Association between complaints of dizziness and hypertension in non-institutionalized elders - Lopes,Anália Rosário (2013)
INTRODUCTION: Advancing age increases the risk for a number of chronic diseases. Hypertension and dizziness are highly prevalent in the elderly population and represent major health problems. OBJECTIVE: To verify the association between complaints of dizziness and the presence of hypertension in non-institutionalized elders. METHODS: This was a prospective cross-sectional cohort study of the elderly population of Londrina, Paraná in terms of aging and longevity. The required sample size was calculated, and subjects e" 60 years of age of both genders were selected at random. Data were collected using a questionnaire covering socio-demographic information and self-reported cases of hypertension and dizziness. Statistical analysis was performed using the chi-square test with p d" 0.05 as the level of significance. RESULTS: The study included 493 elderly subjects, of whom 257 (52.1%) complained of dizziness and 308 (62.5%) reported a diagnosis of arterial systemic hypertension. Dizziness was significantly associated with hypertension (χ² = 6.26, p = 0.01) and female sex. CONCLUSIONS: Hypertension and dizziness were both highly prevalent and were significantly associated, showing the great need for investments in preventive measures.